Maintenance of wetland plant communities: the role of the seed bank in regeneration of native plants - Bao, Francielli [UNESP]; Assis, Marco Antonio De [UNESP]; Pott, Arnildo (Sociedade Botânica do Brasil, 2021)
Exotic grasses have been introduced into wetlands and can compete with native plants due to their high tolerance of flood and dry periods. Flooding can facilitate seed dispersal of exotic species and reduce the diversity of native species. We compared two grasslands to assess whether seed banks can maintain the diversity of native plants in wetlands with introduced exotic plants. We recorded a total of 136 species and a predominance of annual plants in the seed bank and vegetation together. The seed bank had high species diversity independently of the dominance of the exotic Urochloa humidicola in the vegetation. The seed banks of the native and cultivated grasslands differed significantly with a positive correlation for aquatic plants in the native grassland and negative correlation in the cultivated grassland. The seed bank revealed potential to maintain the diversity of native species in the cultivated grassland since the flood and dry seasons promoted the presence of distinct species in the seed bank, but lower richness in the vegetation reflects a dependence on the germination stage. The seasonality of flood and dry periods influences distinct growth forms, increasing the diversity of the seed bank and the vegetation.
Keywords: exotic plants; life cycle; grasslands; growth forms; seasonal savanna